DEVELOPMENT OF A PARAMETRIC PROGRAM FOR PROCESSING A HYPERBOLIC SURFACE ON A LATHE MACHINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This paper discusses the development of a parametric (macro) program for processing a hyperbolic surface on a CNC lathe machine. Analytical dependences have been used to develop the macro program, as a result of which the CNC (computer numerical control) automatically calculates the coordinates of the intermediate points of the tool trajectory. The WHILE cycle operator is used to run the tool. Macro program functionality has been verified in a virtual environment using Vericut.